2020
DOI: 10.1016/j.meegid.2020.104177
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of infectious bronchitis virus in Poland from 1980 to 2017

Abstract: A B S T R A C TThe presence of infectious bronchitis virus (IBV) was identified for the first time in the poultry population in Poland at the end of the 1960s. From this time a few waves of epidemics caused by different IBV variants spread across the country. In order to gain more insight into the molecular epidemiology of IBV in Poland, in the present study the S1 coding region of 34 IBV isolates and nearly whole genome of 10 strains collected over a period of 38 years was characterized. Phylogenetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The virus shows variable tissue tropism and virulence properties, and the immunoprophylaxis is the primary measure to control IBV infections [ 13 ]. The molecular surveillance of IBV exhibited that GI-23 strains are frequently recognised in recent years in Poland [ 11 ]. Field observation showed that the disease outcome was mainly associated with medium respiratory signs and watery diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus shows variable tissue tropism and virulence properties, and the immunoprophylaxis is the primary measure to control IBV infections [ 13 ]. The molecular surveillance of IBV exhibited that GI-23 strains are frequently recognised in recent years in Poland [ 11 ]. Field observation showed that the disease outcome was mainly associated with medium respiratory signs and watery diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the emergence of closely-related Var2 strains was reported in Romania and Germany, indicating the spread of this variant in Europe [ 9 , 10 ]. In Poland, in the following years, the number of Var2 cases had increased accounting for over 28% of all lineages detected between 2018–2019 [ 8 , 11 ]. Six months after the first IBV GI-23 disease outbreak, the registration of the homologous vaccine for this IBV lineage (Tabic IB Var206) was approved by the Polish veterinary authorities, which made a total of five virus types (GI-1 = Mass, GI-(1 + 12) = Mass + D274, GI-13 = 793B, and GI-19 = QX) contained in many live attenuated vaccines available in Poland, which are used in combination or alone.…”
Section: Introductionmentioning
confidence: 99%
“…Igacovirus subgenus contains 3 species : avian coronavirus , avian coronavirus 9203 , and duck coronavirus 2714 . Viruses of Igacovirus subgenus primarily infect birds, such as chickens ( Gallus gallus ), turkeys, ducks, geese, pheasants, partridges, pigeons and peafowl (Cavanagh et al 2002 ; Jonassen et al 2005 ; Cavanagh 2007 ; Sun et al 2007 ; Domanska-Blicharz et al 2020 ). Infectious bronchitis virus (IBV) is the prototype virus of Igacovirus subgenus, and various serotypes of IBV have been identified.…”
Section: The Taxonomy Host Range and Pathogenicity Of Cornidovirineaementioning
confidence: 99%
“…This part of the genome also encodes a few low-molecular-weight accessory proteins whose number and nature vary depending on the species and even the ACoV strain. These proteins would be 3a, 3b, 4b, 4c, 5a, and 5b, although TCoV, GfCoV, and some IBV strains also have an ORF NS6 located downstream of the nucleocapsid protein encoding the 6b protein ( Maurel et al., 2011 ; Ducatez et al., 2015 ; Brown et al., 2016 ; Domanska-Blicharz et al., 2020 ). In addition to their similar genome structure, these strains also have a close genetic relationship as nucleotide similarity of whole genomes between TCoV/GfCoV and IBV strains is higher than 86%.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of IBV was identified for the first time in the chicken population in Poland at the end of the 1960s, and then, a few waves of epidemics caused by different IBV variants appeared every 8–11 yr: GI-1 in 1988, GI-13 in 1997, GI-19 in 2004, and GI-23 in 2015. During this period, IBV strains described as unique early Polish variants and recombinants were also detected ( Domanska-Blicharz et al., 2020 ). In turn, the prevalence of TCoV in the Polish turkey population was estimated at the level of about 6.5%.…”
Section: Introductionmentioning
confidence: 99%